Association between Uric Acid Changes during Hemodialysis and Severity of Left Ventricular Diastolic Dysfunction in ESRD Patients (Journal of Fatima Jinnah Medical University, 2025)
Background: Hyperuricemia has been implicated in cardiovascular disease, the leading cause of mortality in dialysis patients. Elevated SUA can contribute to left ventricular hypertrophy and diastolic dysfunction through pro-inflammatory mechanisms and by impacting metabolic pathways. The role of serum uric acid (SUA) in left ventricular diastolic dysfunction (LVDD), however, remains unclear in patients with end-stage renal disease (ESRD) undergoing hemodialysis. This study is aimed to determine the association of hyperuricemia with left ventricular diastolic dysfunction in end stage renal disease patient on maintenance hemodialysis.Methods: A prospective study was carried on 129 patients with end stage renal disease of either gender of aged between 18 to 70 years who initiated maintenance hemodialysis at our hospital. Before and after hemodialysis, SUA levels were measured via standard enzymatic assay, and LVDD through echocardiographic evaluation followed ASE guidelines.Results: The mean age of the eligible participants was 42.80 ±10.86 years. 65 (50.3%) of the patients were male and 64 (49.6%) were female. Most of the patients had dialysis twice a week 91 (70.5%). The pre-dialysis, uric acid was 6.89 + 1.23 and post-dialysis it reduced to 4.78 + 1.13, significant difference was as p-value was
Keywords: Chronic Kidney disease; Diastolic Dysfunction; End Stage Renal disease; Hemodialysis, Uric acid